2015
DOI: 10.1016/j.rpemd.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and caries among 13-year-old population in Castelo de Paiva, Portugal

Abstract: r e v p o r t e s t o m a t o l m e d d e n t c i r m a x i l o f a c . 2 0 1 5;5 6(1):3-8 a b s t r a c tObjectives: The purpose of this study was to evaluate the association between dental caries and body mass index-for-age (BMI-for-age) in a 13-year-old population. Methods:A cross-sectional study was carried out with a birth-cohort of 181 voluntary 13 yearold adolescents belonging to a grouping of schools in Castelo de Paiva. BMI-for-age, DMFT and oral hygiene habits were recorded. The Z-test, Mann-Whitney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
8
0
4
Order By: Relevance
“…As is well known, dental caries is a disease caused by many factors such as microorganisms, oral habits, genetics, time, and fluoride treatment; thus the sole factor of diet might be influenced or flattened by other factors . Frias-Bulhosa et al [2015] §suggested that oral hygiene habits had more statistical importance in the relation between dental caries and BMI. Thus the conflicting results published over time might in part be conditioned by the frequency and time of executing daily oral hygiene habits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As is well known, dental caries is a disease caused by many factors such as microorganisms, oral habits, genetics, time, and fluoride treatment; thus the sole factor of diet might be influenced or flattened by other factors . Frias-Bulhosa et al [2015] §suggested that oral hygiene habits had more statistical importance in the relation between dental caries and BMI. Thus the conflicting results published over time might in part be conditioned by the frequency and time of executing daily oral hygiene habits.…”
Section: Discussionmentioning
confidence: 99%
“…All the studies were cross-sectional. When classifying articles according to dentition, 4 of them investigated primary dentition [Trikaliotis et al, 2011;Norberg et al, 2012;Bagherian and Sadeghi, 2013;Pikramenou et al, 2016], 6 investigated mixed dentition [Willerhausen et al, 2007;Costacurta et al, 2011;Subramaniam and Singh, 2011;Elangovan et al, 2012;Shahraki et al, 2013;Liang et al, 2016], and the remaining 4 investigated permanent dentition [Narksawat et al, 2009;Sadeghi et al, 2011;Frias-Bulhosa et al, 2015;Denloye et al, 2016]. Of the 6 studies investigating mixed dentition, 4 calculated both primary and permanent teeth [Willerhausen et al, 2007;Costacurta et al, 2011;Subramaniam and Singh, 2011;Elangovan et al, 2012], while 1 just calculated primary teeth [Liang et al, 2016] and the remaining 1 calculated permanent teeth only [Shahraki et al, 2013].…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Studi lain menyatakan bahwa tidak terdapat perbedaan berarti skor DMFT/deft pada anak dengan status gizi yang berbeda. 7,8 Kejadian karies gigi yang banyak terjadi yaitu pada gigi permanen khususnya gigi molar pertama bawah permanen. Penelitian yang dilakukan oleh Kumar et al 9 Pengumpulan data dilakukan dengan pemeriksaan langsung terhadap subyek penelitian, yaitu pengukuran tinggi badan dan berat badan, lalu dikategorikan berdasarkan kategori usia pada TB/U dan IMT/U untuk menilai status gizi.…”
unclassified